Interpretasi dan Implementasi Hak dan Kewajiban Suami Istri dalam Hukum Islam di Masyarakat Patriarkal: Studi Kualitatif di Indonesia: Interpretation and Implementation of Husband and Wife Rights and Obligations in Islamic Law in Patriarchal Society: A Qualitative Study in Indonesia - Muhamat Mubin; Nirwana, Andi; Azizah, Alfiyatul; Nurrohim, Ahmad; Dahliana, Yeti; Burhanudin Al-Ghoni (Litera Academica Publishing, 2025)
This study examines the interpretation and implementation of the rights and obligations of husband and wife in Islamic law in Indonesian patriarchal society. This study uses a qualitative approach with a literature study method to analyze how Islamic law is interpreted and implemented in the context of patriarchal culture. The findings of the study suggest that patriarchal culture often leads to imbalances in the exercise of the rights and obligations of husband and wife, with husbands tending to have a dominant role in decision-making. In contrast, wives are more involved in domestic work and childcare. This research emphasizes the importance of increasing awareness and understanding of the rights and obligations of husband and wife in Islamic law, as well as reducing the influence of a patriarchal culture that is not by the principles of justice and balance in Islam. The results of this study are expected to provide insights and recommendations to improve balance and justice in marital relations in Muslim communities.